치아홈메우기의 건강보험 급여화와 치과위생사 시술에 대한 학부모의 인식 및 태도 - 김윤정; Yun Jeong Kim (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The purpose of this study was to investigate parents`` recognition and attitudes toward national health insurance coverage of sealant by the dental hygienists. Methods: A self-reported questionnaire was filled out by 329 elementary school children parents in G metropolitan city and N city from July 11 to 27, 2015. The questionnaire consisted of general characteristics of the subjects, recognition and attitudes toward national health insurance coverage of sealant and sealant by the dental hygienist, and recognition toward national health insurance. The data were analyzed by a descriptive analyses, multiple regression and logistic regression analysis using SPSS 12.0 program. Results: Recognition of national health insurance coverage was 2.52 times higher in high school and 4.97 times higher in recognition toward purpose of sealant. Factor affecting recognition of national health insurance was subscription of private health insurance, recognition of sealant treatment by dental hygienist (DH) and recognition of national health insurance coverage of sealant. Attitude toward sealant treatment by DH was positive in experience of sealant, recognition of sealant treatment by DH and experience of sealant treatment by DH. Factor affecting satisfaction on the sealant by DH was recognition of sealant treatment by DH and recognition of purpose of sealant. Conclusions: To increase national health insurance coverage of sealant, it is necessary to expand positive public relations of sealant by the dental hygienist.